THE USE OF TECHNOLOGIES IN ENGLISH LANGUAGE TEACHING - Tetiana I. Cybaniuk; Olena V. Kraiova (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
In the early part of the 21st century the range of technologies available for use in language learning and teaching has become very diverse and the ways that they are being used in classrooms all over the world have become central to language practice. Technology in its various forms has long been used in ESP, whether in the form of a tape recorder or sophisticated digital technology. But maybe its impact on ESP has been more profound. ESP teachers have always used available tools to devise materials and create situations relevant to their students’ needs. The present article focuses on the role of technologies in English language learning and teaching showing the benefits of technology use in ELT. It also deals with the challenges which the teachers and institutions that integrate technology in their ELT can face.